Syndromic management of sexually transmitted infections among female sex workers in Lomé (Togo), 2023 - Oumarou I. Wone Adama; Iman Frédéric Youa; Alexandra Bitty-Anderson; Arnold Junior Sadio; Rogatien Comlan Atoun; Yao Rodion Konu; Hezouwe Tchade; Martin Kouame Tchankoni; Kokou Herbert Gounon; Kparakate Bouboune Kota-Mamah; Abissouwessim Egbare Tchade; Godonou Amivi Mawussi; et al. (PLoS ONE, 2025)
Introduction In Togo, the syndromic approach is used for the diagnosis and management of sexually transmitted infections (STIs). The aim of this study was to evaluate the syndromic approach for diagnosis of STIs among female sex workers (FSW) in Lomé, Togo. Methods A cross-sectional study was carried out from September to October 2023 among FSW in Lomé (Togo). FSW aged 18 years and above were included. A gynecological examination was performed for syndromic diagnosis, and the Xpert® CT/NG were used to screen vaginal swabs for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG). The performance (predictive values) of the syndromic approach to STI diagnosis was evaluated using the Xpert® CT/NG test as the gold standard. Results A total of 357 FSW were recruited. The median age of FSW was 32 years (IQR: [26–40 years]) and 8.2% had attained a higher level of education. The prevalence of syndromic STI among FSW was 33.3%. Vaginal swabs were positive for CT (8.4%) and NG (8.7%), with a prevalence of bacterial STIs (CT and/or NG) of 14.3%. The syndromic approach to STI diagnosis demonstrated a positive predictive value of 24.3%. Conclusion The prevalence of STIs is relatively high among FSW in Lomé. According to this study, the diagnosis of STIs using the syndromic approach has limited relevance. National STI screening and management policies urgently need to be rethought, incorporating recent technological advances.